2012
DOI: 10.1021/cg3000312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solution Thermal and Structural History on the Nucleation of m-Hydroxybenzoic Acid Polymorphs

Abstract: The influence of solution pre-treatment on primary nucleation of m-hydroxybenzoic acid has been investigated through 550 cooling crystallization experiments. The metastable zone width has been determined at constant cooling rate and the time and temperature of the preceding superheating step have been varied. m-Hydroxybenzoic acid has two polymorphs and the influence of the polymorph used to prepare the solutions has also been investigated. There is an overall tendency in the experiments for the solution to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 37 publications
(65 reference statements)
1
43
0
Order By: Relevance
“…13 This initial set of induction times will be referred to as "first nucleation", the procedure being almost identical to that used by Nordström et al to demonstrate solution history effects on polymorphism. 9 The time to reach a temperature deviating by 1 °C from the final value was measured to be approximately 1 minute (Dostmann P750 with Pt100 immersion probe, accuracy 0.03 °C). It took about 7 minutes to reach the nucleation temperature within 0.03 °C.…”
Section: Methodsmentioning
confidence: 99%
“…13 This initial set of induction times will be referred to as "first nucleation", the procedure being almost identical to that used by Nordström et al to demonstrate solution history effects on polymorphism. 9 The time to reach a temperature deviating by 1 °C from the final value was measured to be approximately 1 minute (Dostmann P750 with Pt100 immersion probe, accuracy 0.03 °C). It took about 7 minutes to reach the nucleation temperature within 0.03 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Each batch was kept at an elevated temperature of 60 °C for 6 h, and then at 55 °C for another 6-10 h, in order to standardize the pre-treatment of solutions and minimize effects of solution history 16,24 . The test tubes were then cooled at a constant cooling rate of either 3 °C/h or 10 °C/h.…”
Section: Nucleation Experimentsmentioning
confidence: 99%
“…The structure of the thermodynamically stable polymorph at room temperature 12 , henceforth termed form I, contains the carboxylic acid dimer motif packed in the common herring-bone pattern, whereas that of the metastable polymorph, form II, features intermolecular hydrogen bond chains involving alternate COOH and OH-groups, creating layers of ribbons where the non-polar regions of neighbouring ribbons interact through van der Waals' forces. In a previous contribution we gave an account of experiments probing the influence of the thermal and structural history of solution on the nucleation of mHBA polymorphs in ethyl acetate solution 16 . Here, we report a quantitative investigation into the thermodynamic properties of both polymorphs, and into the nucleation behaviour in five different solvents.…”
Section: Introductionmentioning
confidence: 99%
“…This technique of recording the induction time has been evaluated in smaller scale for these systems in previous contributions 4,5 and has been successfully applied in several previously reported studies, with the proviso that the visible onset of the event be sufficiently rapid. 11,13,14 In a comparative study of nucleation detection methods, it was shown for nucleation of paracetamol in a stirred crystallizer that the accuracy of using the naked eye is quite comparable to that obtained by FBRM and FTIR spectroscopy. 15 For the experiments with butyl paraben in ethanol, after nucleation was recorded in the three vessels, the circulation water was switched to the higher temperature, and the whole procedure repeated, for a total of up to 10 times for each solution.…”
Section: Nucleation Experimentsmentioning
confidence: 91%
“…13,16,17 The agitation rate was changed in a random pattern between experiments. For the experiments with mHBA in 1-propanol, as soon as sufficient crystalline material had precipitated in a vessel (between 10-15 min after nucleation was observed), the contents were filtered (Munktell grade 00A filter paper) and dried in a ventilated fume hood.…”
Section: Nucleation Experimentsmentioning
confidence: 99%